(untitled) (Journal of the Association for the Study of Australian Literature, 2014)
The tendency for Western cultures to emphasise imperial attitudes and experiences in their literature has been described by Edward Said as the primary means by which colonised people assert their identity and the existence of their own history (xii). The tradition of Australian children’s literature, which first grew out of contributions made by European colonisers and largely ignored any indigenous past has been referred to as a “product of colonial history” (Bradford, “Representing Indigeneity” 90) and “a shamelessly racist catalogue of prejudice and misinformation, of superficial clichés, offensive stereotyping and entirely subjective interpretation” (McVitty 7). Historians Robert Hodge and Vijay Mishra use the term Aboriginalism – a variation of Said’s notion of Orientalism – to describe the way in which colonial powers traditionally constructed ideas about the colonised other within patterns of discourse, aptly masking their racist objective and appearing to function constructively (27). Focusing on three Australian children’s texts translated into German, this paper examines how the notion of Aboriginality – at different points in time – is presented in the source text and dealt with in translation. While consideration of the purpose – the skopos (Vermeer 1989/2004) – of the translation forming the backbone of contemporary translation theory, the so-called aims of children’s literary translation also cast an important light on the way in which translation strategies are informed. Furthering the international outlook and understanding of young readers remains the most commonly agreed-upon objective of children’s literary translation. In real terms, the execution of this aim often comes down to the decision to foreignise or domesticate. The problem, as translator Anthea Bell writes, is that “one wants readers of the translated text to feel that they are getting the real book, as close as possible to the original”, but which – vitally – includes respecting the foreign aspects of the source text (62). Yet translators of children’s literature (unlike translators of adult literature) have the added challenge of having to negotiate a variety of what Katharina Reiss calls ‘Vermittlerinstanzen’ (intermediaries): parents, teachers, librarians and publishers, who place pressure on the translator (in regards to taboos and pedagogical aspects of the text), so much so that the outcome (i.e. the target text) is affected (7).